Mixed phase within the multi‐polytrope approach to high‐mass twins. Issue 9 (28th November 2017) - Alvarez‐Castillo, D.; Blaschke, D.; Typel, S.
Abstract : We present a multi‐polytrope approach to describe high‐mass twins fulfilling chiral effective field theory estimations of the neutron star equation of state and test it against the appearance of mixed phases at the hadron–quark interface. In addition, we discuss astrophysical applications of this method and the expected future measurements that will further constrain neutron star matter and the understanding of the quantum chromodynamics phase diagram.